2014
DOI: 10.1002/mbo3.188
|View full text |Cite
|
Sign up to set email alerts
|

Affinity maturation of Cry1Aa toxin to the Bombyx mori cadherin‐like receptor by directed evolution based on phage display and biopanning selections of domain II loop 2 mutant toxins

Abstract: Directed evolution of a Cry1Aa toxin using phage display and biopanning was performed to generate an increased binding affinity to the Bombyx mori cadherin-like receptor (BtR175). Three mutant toxins (371WGLA374, 371WPHH374, 371WRPQ37425) with 16-, 16-, and 50-fold higher binding affinities, respectively, for BtR175 were selected from a phage library containing toxins with mutations in domain II loop 2. However, the observed toxicities of the three mutants against B. mori larvae and cultured cells expressing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…PC has an LC 50 value of 77 μg/per larvae. In contrast, Cry1A toxin has an LC 50 value of 1 ng per square cm or a few hundred nanograms for B. mori instar larvae (less than 200 ng/cm 2 ) indicating that PC is at least 400-fold less toxic 8 46 . The shortcoming of low toxicity of PC may be a limitation for its utility in pest control.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…PC has an LC 50 value of 77 μg/per larvae. In contrast, Cry1A toxin has an LC 50 value of 1 ng per square cm or a few hundred nanograms for B. mori instar larvae (less than 200 ng/cm 2 ) indicating that PC is at least 400-fold less toxic 8 46 . The shortcoming of low toxicity of PC may be a limitation for its utility in pest control.…”
Section: Discussionmentioning
confidence: 96%
“…Toxins are important virulence factors for bacterial pathogenicity. Interactions with single receptors are a general strategy, although several toxins such as diphtheria, Cry, or aerolysin toxins target more than one surface molecule in their binding activities and action modes 8 . Here, we demonstrated that binding to BmAPN4 provokes the pathogenicity of PC ( Figs 2 and 3 ), although the kinetic parameters of the interaction between PC with APN have not been fully analysed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations